THE LEGAL REGULATORY FRAMEWORK OF SHARIA SECURITIES CROWDFUNDING IN INDONESIA - Afif Noor (Faculty of Law, Universitas Diponegoro, 2022)
The Sharia SCF industry is thriving in Indonesia with an increasing number of providers and users, but it is also very high risk. To establish trust and ensure investment security, a strong legal framework is needed. This study uses a statutory approach to examine the legal regulatory framework for Sharia SCF. The research found that while Article 33 of the 1945 Constitution forms the basis of Sharia SCF regulations, the industry is not specifically regulated by law. Instead, the Financial Services Authority issued POJK No. 57/2020 based on Law No. 21/2011. However, in the future, the Sharia SCF industry must be regulated by law to provide maximum legal certainty and protection for users or consumers.